Evaluation of the accuracy of common weight estimation formulae in a Zambian paediatric surgical population. (27th December 2016) - Bowen, L.; Zyambo, M.; Snell, D.; Kinnear, J.; Bould, M. D.
Summary: Limited resources and access to healthcare in sub‐Saharan Africa are associated with high rates of malnourished children, although many countries globally are demonstrating increasing childhood obesity. This study evaluated how well current age‐ or height‐based formulae estimate the weight of children undergoing surgery in Zambia. All children under 14 years of age presenting for elective surgery at the University Teaching Hospital, Lusaka, had both height and weight measured. Their actual weight was compared against estimated weight from various formulae. The Broselow tape outperformed all the age‐based formulae, demonstrating the lowest median percentage error of −5.8%, with 46.0% of estimates falling within 10% of the actual measured weight (p < 0.001). Of the 1111 children who were eligible for World Health Organization growth standard appraisal, 88 (8%) met the weight criteria for severe acute malnutrition. Our results are consistent with other studies in finding that the Broselow tape is the best estimator of weight in a lower middle‐income country, followed by the original Advanced Paediatric Life Support formula if the Broselow tape is unavailable.